Dispersion of Particle‐Reactive Elements Caused by the Phase Transitions in Scavenging. Issue 10 (17th October 2022) - Maderich, V.; Kim, K. O.; Brovchenko, I.; Jung, K. T.; Kivva, S.; Kovalets, K.
Abstract: A generalized model of scavenging of the reactive radionuclide 239, 240 Pu was developed, in which the sorption‐desorption processes of oxidized and reduced forms on multifraction suspended particulate matter are described by first‐order kinetics. One‐dimensional transport‐diffusion‐reaction equations were solved analytically and numerically. In the idealized case of instantaneous release of 239, 240 Pu on the ocean surface, the profile of concentrations asymptotically tends to the symmetric spreading bulge in the form of a Gaussian moving downward with constant velocity. The corresponding diffusion coefficient is the sum of the physical diffusivity and the apparent diffusivity caused by the reversible phase transitions between the dissolved and particulate states. Using the method of moments, we analytically obtained formulas for both the velocity of the center mass and apparent diffusivity. It was found that in ocean waters that have oxygen present at great depths, we can consider in the first approximation a simplified problem for a mixture of forms with a single effective distribution coefficient, as opposed to considering the complete problem. This conclusion was confirmed by the modeling results for the well‐ventilated Eastern Mediterranean. In agreement with the measurements, the calculations demonstrate the presence of a maximum that is slowly descending for all forms of concentration. The ratio of the reduced form to the oxidized form was approximately 0.22–0.24. At the same time, 239, 240 Pu scavenging calculations for the anoxic Black Sea deep water reproduced the transition from the oxidized to reduced form of 239, 240 Pu with depth in accordance with the measurement data. Plain Language Summary: Scavenging of particle‐reactive elements is the process of the removal of a dissolved element in seawater by adsorption onto sinking particulate matters that finally deposit on the ocean floor. Scavenging is an important pathway for the transfer of nutrients and trace elements in the ocean. The radioactive isotopes of artificial origin are useful tools to provide constraints on the scavenging and organic particle removal processes. A generalized model of scavenging of reactive radionuclide 239, 240 Pu was developed, in which the processes of sorption‐desorption of oxidized and reduced forms of plutonium on multifraction particulate matter are described by the first‐order kinetics. We revealed that the vertical spread out of the cloud of plutonium isotope was caused by a novel dispersion mechanism equivalent to the diffusion process. The corresponding dispersion coefficient is the sum of the physical diffusivity and the apparent diffusivity caused by the reversible phase transition between the dissolved and particulate states. It was found that apparent diffusivity for scavenging large particles was several orders of magnitude greater than physical diffusivity in the deep ocean. The model reproduces striking differences in plutonium profiles in ventilated Eastern Mediterranean and the anoxic Black Sea caused by the interplay between oxidized and reduced forms. Key Points: Novel scavenging mechanism due to the reversible phase transition results in apparent diffusivity which surpasses the ocean diffusivity In the well‐ventilated Eastern Mediterranean, the ratio of the reduced form to the oxidized form of 239, 240 Pu was approximately 0.22–0.24 The 239, 240 Pu profile in the Eastern Mediterranean has one maximum, whereas in the anoxic Black Sea it has two maximums